Determinants of Morbidities and Occupational Hazards among Scuba Divers in Andaman and Nicobar Islands, India - Vivin Vincent; Kalyani Ramakrishnan; Shivshankar Singh; Jeevithan Shanmugam (Journal of Pharmacy and Bioallied Sciences)
Background: Occupational health hazards pose significant risks in unique work environments such as scuba diving. This investigation aims to assess health profiles and occupational health determinants among scuba instructors in the Andaman and Nicobar Islands. Materials and Methods: A cross-sectional survey was conducted among certified scuba instructors in the Andaman and Nicobar Islands during 2022–2023 by using a self-administered questionnaire. Data analysis was performed using SPSS version 25. Ethical approval was granted by the institutional ethical committee. Results: The study population comprised 423 male instructors with a mean age of 26.24 ± 4.71 years. They averaged 9 ± 5.2 years of diving experience and 4 ± 3.86 years as instructors. Physical injury underwater was the most prevalent hazard, experienced by 10.4% of participants. There was a positive correlation between the instructors’ knowledge of health and safety and their years of experience. Conclusion: The scuba instructors displayed elevated levels of anxiety and depression, likely due to the high risks associated with their job.